The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1017/s1751731111001467
|View full text |Cite
|
Sign up to set email alerts
|

Does increasing milk yield per cow reduce greenhouse gas emissions? A system approach

Abstract: Milk yield per cow has continuously increased in many countries over the last few decades. In addition to potential economic advantages, this is often considered an important strategy to decrease greenhouse gas (GHG) emissions per kg of milk produced. However, it should be considered that milk and beef production systems are closely interlinked, as fattening of surplus calves from dairy farming and culled dairy cows play an important role in beef production in many countries. The main objective of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
65
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 21 publications
2
65
2
Order By: Relevance
“…A more global consideration is the environmental impact of beef production from the dairy v. the beef herd. As the animal maintenance cost of the dam is shared between milk and calf production, the perceived environmental impact of beef from the dairy herd is lower than that from dedicated beef herds (Zehetmeier et al, 2012). If cows had persistent lactations and did not require re-calving to stimulate milk production, periodic calving to produce beef calves with a short dry period may be environmentally and economically sustainable.…”
Section: Reproductive Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more global consideration is the environmental impact of beef production from the dairy v. the beef herd. As the animal maintenance cost of the dam is shared between milk and calf production, the perceived environmental impact of beef from the dairy herd is lower than that from dedicated beef herds (Zehetmeier et al, 2012). If cows had persistent lactations and did not require re-calving to stimulate milk production, periodic calving to produce beef calves with a short dry period may be environmentally and economically sustainable.…”
Section: Reproductive Targetsmentioning
confidence: 99%
“…If cows had persistent lactations and did not require re-calving to stimulate milk production, periodic calving to produce beef calves with a short dry period may be environmentally and economically sustainable. However, the interactions between these systems are complex (Zehetmeier et al, 2012).…”
Section: Reproductive Targetsmentioning
confidence: 99%
“…For both grazing and confinement systems, the modelling methodology or the assumptions taken may in fact be a large source of uncertainty in the estimation of GHG emission O'Brien et al, 2011;Zehetmeier et al, 2012;Del Prado et al, 2013). For example, in studies of Zehetmeier et al (2012) and Del large differences were found after replacing the default equation Data collected from three different studies (Supplementary Table S3).…”
Section: Assessing Farm-scale Ghg Emissions and Potentials For Mitigamentioning
confidence: 99%
“…For example, in studies of Zehetmeier et al (2012) and Del large differences were found after replacing the default equation Data collected from three different studies (Supplementary Table S3). …”
Section: Assessing Farm-scale Ghg Emissions and Potentials For Mitigamentioning
confidence: 99%
“…Nevertheless, Casey & Holden (2005) calculated GHG emissions ranged from 0.9 to 1.5 kg CO 2 equivalent per litre of milk in typical Irish dairy cattle farms and found a negative relationship between GHG emissions and the intensity of milk production, being comparable with the present study. In addition, increasing milk yield/cow will reduce GHG emissions, if these emissions are expressed per kg milk and reduction in associated beef production is not considered (Zehetmeier et al, 2012).…”
mentioning
confidence: 99%